1998
DOI: 10.1128/aac.42.5.1115
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activity of a Single-Dose Combination of Ofloxacin plus Minocycline, with or without Rifampin, against Mycobacterium leprae in Mice and in Lepromatous Patients

Abstract: To develop a fully supervisable, monthly administered regimen for treatment of leprosy, the bactericidal effect of a single-dose combination of ofloxacin (OFLO) and minocycline (MINO), with or without rifampin (RMP), against Mycobacterium leprae was studied in the mouse footpad system and in previously untreated lepromatous leprosy patients. Bactericidal activity was measured by the proportional bactericidal method. In mouse experiments, the activity of a single dose of the combination OFLO-MINO was dosage rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 18 publications
1
30
2
1
Order By: Relevance
“…They can be administered to patients presenting with an intolerance, resistance, or clinical failure to first-line agents. Patients presenting with rifampicin-resistant leprosy need to take those antibiotics daily, and treatment duration must be extended to 24 months because of a lower bactericidal activity compared with rifampicin [33,59].…”
Section: Second-line Agents: Fluoroquinolones Minocycline and Clarimentioning
confidence: 99%
“…They can be administered to patients presenting with an intolerance, resistance, or clinical failure to first-line agents. Patients presenting with rifampicin-resistant leprosy need to take those antibiotics daily, and treatment duration must be extended to 24 months because of a lower bactericidal activity compared with rifampicin [33,59].…”
Section: Second-line Agents: Fluoroquinolones Minocycline and Clarimentioning
confidence: 99%
“…In vitro experiments demonstrated that fusidic acid is highly bactericidal [97]; but in a Phase II trial, it was only weakly bactericidal [93]. Likewise, Ji et al observed bactericidal activity in mice after 1 month of MDT (99.95%) were similar to that with a single dose of RFM, clarithromycin, OFL and MIN (99.4%) [74]. However, single-dose ROM treatment has been insufficient in humans [87].…”
Section: Is It Possible To Translate the Existing Preclinical Trials mentioning
confidence: 96%
“…Either no information on the comparable characteristics of the volunteer participants at intake was included, or the study groups were significantly different upon enrollment in some of the key end points evaluated. The study by Ji et al is a case in point: the mean patient MI in the group receiving ROM was significantly smaller than the one receiving OFL-MIN (p = 0.001) [74].…”
Section: Clinical Trials With Non-who-mdt Drugsmentioning
confidence: 97%
See 1 more Smart Citation
“…Leprosy is a chronic infectious disease caused by Mycobacterium leprae and mainly affects the skin and peripheral nerves. In addition, Leprosy is a major global health problem in several countries of Asia, Latin America, and Africa (Ji et al, 1998;Maeda et al, 2001). Leprosy is effectively controlled by a multidrug therapy (MDT) regimen of dapsone, rifampicin, and clofazimine.…”
Section: Introductionmentioning
confidence: 99%